2010
DOI: 10.5021/ad.2010.22.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Extracellular Matrix Production in Dermal Fibroblasts by Velvet Antler Extract

Abstract: Background:Fibroblasts produce many components of the extracellular matrix (ECM) and so they contribute to the maintenance of connective tissue integrity. Objective: The aim of this study is to evaluate the effect of velvet antler extract (VAE) on the ECM production of dermal fibroblasts cultured in vitro. Methods: Primary cultured human dermal fibroblasts were treated with VAE, and then the ECM production was determined by RT-PCR, ELISA and Western blot analysis. Furthermore, the change of gene expression acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, the precise interaction between these events and MAPKs in CCD986sk fibroblasts in response to DCF absolutes will need to be clarified in future studies. In addition, collagen synthesis by skin fibroblasts is known to be related to the TGF-β-mediated signaling pathway that can mediate the activation of MAPKs [39][40][41]. It has been demonstrated that type I and IV collagens may be produced by Erk1/2 or/and p38 MAPK activation in fibroblasts exposed to various molecules, including TGF-β1 [35,39,[41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…However, the precise interaction between these events and MAPKs in CCD986sk fibroblasts in response to DCF absolutes will need to be clarified in future studies. In addition, collagen synthesis by skin fibroblasts is known to be related to the TGF-β-mediated signaling pathway that can mediate the activation of MAPKs [39][40][41]. It has been demonstrated that type I and IV collagens may be produced by Erk1/2 or/and p38 MAPK activation in fibroblasts exposed to various molecules, including TGF-β1 [35,39,[41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…26) On the other hand, the TGF-β-mediated activation of ERK signaling promoted collagen synthesis in human mesangial cells and human osteoblasts. 28,29) It has also been reported that a velvet antler extract, which is known to activate ERK, promotes type I collagen synthesis in human dermal fibroblasts. 30) In our study, treatment with the PPE increased expression levels of TβRII mRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports on proteome analysis of cartilage [10] and bone [11], the sequential protein extraction method improved significantly the number of identified proteins, suggesting that more proteins might be extracted if multiple complementary extraction buffers were sequentially used. In addition, many studies have demonstrated that the extracts of velvet antlers possessed widely biological activities [12][13][14]. For the simultaneous assessment of the bioactivities of extracted proteins, the biocompatible extraction buffers should be selected to prevent extracted proteins from denaturation.…”
Section: Introductionmentioning
confidence: 99%